2021
DOI: 10.1016/j.resp.2021.103769
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation and deposition of spherical and pollen particles after middle turbinate resection in a human nasal cavity

Abstract: Middle turbinate resection significantly alters the anatomy and redistributes the inhaled air. The superior half of the main nasal cavity is opened up, increasing accessibility to the region. This is expected to increase inhalation dosimetry to the region during exposure to airborne particles. This study investigated the influence of middle turbinate resection on the deposition of inhaled pollutants that cover spherical and non-spherical particles (e.g. pollen). A computational model of the nasal cavity from C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Fungal hyphae can be found on sinonasal aspirate smears in the sinuses of AFRS patients under microscopes [38]. Inthavong K et al found that both spherical and nonspherical pollens could be deposited in the nasal sinuses by simulating pollen deposition in the nasal cavity at 5 L/min and 15 L/min inspiratory flow rates; with an increase in the inspiratory flow rate, the deposition rate of pollen in the nasal sinuses and nasal cavity increased, and the deposition position in the nasal cavity moved forward [39]. Using CFD simulation of 60 nasal chambers of healthy subjects, our study also found that although the deposition rate of A. niger spores in the nasal cavity was relatively small, a varied number of spores could be found in the maxillary sinuses of all models (0.30-0.45%), providing potential nasal aerodynamic evidence for the occurrence of AFRS in the maxillary sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal hyphae can be found on sinonasal aspirate smears in the sinuses of AFRS patients under microscopes [38]. Inthavong K et al found that both spherical and nonspherical pollens could be deposited in the nasal sinuses by simulating pollen deposition in the nasal cavity at 5 L/min and 15 L/min inspiratory flow rates; with an increase in the inspiratory flow rate, the deposition rate of pollen in the nasal sinuses and nasal cavity increased, and the deposition position in the nasal cavity moved forward [39]. Using CFD simulation of 60 nasal chambers of healthy subjects, our study also found that although the deposition rate of A. niger spores in the nasal cavity was relatively small, a varied number of spores could be found in the maxillary sinuses of all models (0.30-0.45%), providing potential nasal aerodynamic evidence for the occurrence of AFRS in the maxillary sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the nozzle diameter (the diameter of injection of particles at the inlet) on the aerosol deposition and transport pattern was also studied using computational fluid dynamics (CFD) modelling. CFD is an advantageous noninvasive tool to study the airflow behaviour and particle transport pattern in the upper and lower airways (Inthavong et al 2021 ; Islam et al 2021 ; Rahman et al 2021 ; Salati et al 2021 ; Singh et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, indoor air quality can significantly affect human health and comfort, because air is vital to humans. Many previous studies have investigated inhalation‐related health risks, using numerical analysis techniques and computational modeling of the human respiratory tract and the breathing process 14–20 . Moreover, many studies have focused on the integrated analysis (combining indoor spaces and the respiratory tract) and its application to indoor environmental design 12,21,22 .…”
Section: Introductionmentioning
confidence: 99%